Characteristic Trend of Persistent Organochlorine Contamination in Imported Red Kidney Beans: Organochlorine Contamination in Red Kidney Beans (Biological Sciences - PJSIR, 2010)
Residual level of persistent organochlorines (OC) such as SHCH, dieldrin and endrin were measured in red kidney bean samples from consignments imported from Ethiopia during 2004-2006. OCs, mainly SDDT and SHCH along with breakdown products (>65%), were detected in 80% of the samples analyzed and the highest concentration was 37 ng/g. In 2004, 20% and in 2006, 40% samples were found contaminated with detectable levels of OCs. Beta-HCH, however, was not detected in any sample in 2004 and HCB, in 2005. In 2004, average residual concentration of OCs in individual sample was 0.03-0.180 mg/kg and in 2005, 0.004-0.09 mg/kg.